Marx for a postcommunist era :on poverty, corruption, and banality - Sullivan, Stefan (Routledge, 2002)
Marx for a Post-Communist Era combines a deep understanding of Marxist thought with journalistic engagement in real-world themes. This comprehensive and timely book will be of interest to students and academics in the areas of philosophy, sociology, politics and cultural studies, and to anyone with an interest in Marx and his legacy.